Comparing Sensitivity of Ultrasonography and Plain Chest Radiography in Detection of Pneumonia; a Diagnostic Value Study - Ebrahim Karimi (Archives of Academic Emergency Medicine, 2019)
Introduction: Rapid detection of pneumonia and early initiation of antibiotic therapy are associated with better prognosis in patients. The present study was designed aiming to evaluate the sensitivity of chest ultrasonography performed by emergency medicine specialists in detection of pneumonia and comparing it with plain radiography.